A Preliminary Study of Necrophagous Flies (Insecta: Diptera) in the Lhasa Region (Qinghai–Tibet Plateau), China. Issue 2 (24th November 2021) - Shen, Xiao; Jiang, Yangshuai; Shang, Yanjie; Wang, Yuanxing; Guo, Shaojiang; Guo, Nan; Yang, Junbo; Cai, Jifeng; Guo, Yadong; Zhang, Changquan
Abstract: Lhasa is located on the Qinghai–Tibet Plateau, with an altitude of 3, 650 m, and a unique geography. Its climate is dry and cold all year round. Forensic entomological studies of the region are scarce. In this study, the diversity and seasonality of necrophagous flies in eight counties among Lhasa region were determined, and succession of necrophagous flies colonizing on rabbits in the Chengguan area of Lhasa was studied, so as to provide reference data for estimating postmortem interval (PMI) and location of death. In total, 22 species of necrophagous flies, belonging to six families were identified in Lhasa. Protophormia terraenovae (Robineau-Desvoidy, 1830) (Diptera: Calliphoridae) was the dominant species throughout the year, the diversity index (4.5834) indicated that the study on necrophagous flies in the Lhasa region is representative.